(1)-2²÷(-2分之1)的4次方×(-1)的8次方-(1又8分之3+2又3分之1-3又4分之3)×24

来源:学生作业帮助网 编辑:作业帮 时间:2024/07/13 15:54:06
(1)-2²÷(-2分之1)的4次方×(-1)的8次方-(1又8分之3+2又3分之1-3又4分之3)×24
xn0_%pB@"V>DHIEPtnٳU3r( C/9J#j@%߾c7w7]___46X;!}Bnb$̥J9x5JvOG{'W^yWL;ݠ(b2A:9ߊr&kPƙVIiȌ}TKm2%ę'mT,>*㊪dꢢ~wflU:HG&EPD]x]QwYZʆL5 ࠛ9mv8!}Cdc6u$]j9co/PmY#k*dbDv )64D\;@IWHౠ(B؆5غ

(1)-2²÷(-2分之1)的4次方×(-1)的8次方-(1又8分之3+2又3分之1-3又4分之3)×24
(1)-2²÷(-2分之1)的4次方×(-1)的8次方-(1又8分之3+2又3分之1-3又4分之3)×24

(1)-2²÷(-2分之1)的4次方×(-1)的8次方-(1又8分之3+2又3分之1-3又4分之3)×24

(1)-2²÷(-2分之1)的4次方×(-1)的8次方-(1又8分之3+2又3分之1-3又4分之3)×24
=-4÷1/16×1-1又3/8×24-2又1/3×24+3又3/4×24
=-64-33-56+90
=-63


-2的2次方÷(-2分之1)的4次方X(-1)的8次方-(1又8分之3+2又3分之1-3又4分之3)X24
=-4÷1/16×1-(11/8+7/3-15/4)×24
=-4÷1/16×1-(33/24+56/24-90/24)×24
=-4÷1/16×1+1/24×24
=-64+1
=-63